The influence of incidental haptic sensations in evaluating consumer brands - Leigh Leo; Elizabeth Swinstead; Freddie Crous; Gideon Pieter de Bruin (Communicare)
Embodied cognition provides the epistemological means from which new insights into haptic sensations can be explored within the field of consumer psychology. Extant research has shown that incidental haptic sensations can, nonconsciously, influence the judgement of objects that are non-diagnostic (unrelated) for the actual qualities of the item being judged; this would include the perception customers have of products. The application of this conception to the use of selfreport questionnaires in consumer research lead to the hypothesis that the haptic experience of a self-report questionnaire (weight and firmness of the paper) could, nonconsciously, trigger physically grounded mental frameworks. In turn, this could lead consumers to form stronger product judgments when encountering an incidental, tactile experience of strength (firmness) in a self-report questionnaire. In two experiments (N = 178 and N = 128) evidence was found to support this hypothesis. Implications of the findings and future research directions are discussed.